AMALAN PENULISAN PENGHAKIMAN DAN PELAKSANAANNYA DI MAHKAMAH SYARIAH MALAYSIA: The Practice of Judgement Writing and Its Application in Shariah Court of Malaysia - Razali, Mastura; Sulong, Jasni (Jurnal Syariah, 2017)
The practice of judgement writing is one of the necessary procedures carried out by a judge after trial. This practice is essential for trials at the higher court levels. Therefore, this article explores the history of the judgment writing practice, the significance of judgment writing, and its implementation in Malaysia Shariah Court. This article applies the library research method to gain insight into the practice of judgement writing as applied in the Islamic judiciary institutions. The result of this study has shown that judgment writing has been through various phases of improvement, from the time of the Umayyad Dynasty up until the present day. In addition, this study also found that the practice of judgment writing has now become a requisite in order to achieve justice and equality in law.